A Study of Error Analysis in Aceh - Rezki Nuarta; Usman Kasim; Yuliana Natsir (Research in English and Education Journal, 2016)
The goal of this study is intended to figure out what errors of surface strategy made by the students of SMP Negeri 4 Banda Aceh in writing are. The subject of this study was the eighth grade students. Qualitative study was used as a method to obtain the data. To collect the data, the students’ writings were taken from the teachers in the form of journal text. The technique used in analyzing the data was the technique suggested by Corder (1974) which involves choosing the language corpus, identifying errors in the corpus, classifying errors, explaining errors and evaluating errors. However, to classify the errors, the writer used surface strategy taxonomy suggested by Dulay et.al. (1982). It shows that all of the students produced the errors in surface strategy including omission, addition, misformation and misordering. The most dominant error was omission and it was followed by misformation, addition and misordering. The students also made non surface strategy errors including past tense, spelling, identifying the noun, creating ideas, and capitalization.